COMMUNITY BASED TOURISM: KAJIAN LITERATUR SISTEMATIK BERDASARKAN JURNAL INTERNASIONAL BEREPUTASI TERINDEKS SCOPUS (2018-2023) - Puri Suheri, Syaidina; Zarkasyi Rahman, Amni (Journal of Public Policy and Management Review, 2025)
In Indonesia, research on Community Based Tourism has been widely conducted. However, mapping of the topics and novelty of these studies has not been done. Therefore, this study uses a Systematic Literature Review to map the scientific structure of Community Based Tourism in Indonesia today. Using PRISMA Flow The stages carried out start from identification of publication collection from Scopus, determining keywords, then the screening stage so that data extraction, eligibility, namely the stage carried out by reading the whole by looking at the title and literature extract, and finally the included stage. The results of the analysis for research that is in accordance with the topic and research questions are the development of knowledge on the topic of Community Based Tourism. The results of the study showed an increase in terms of the number of publications and the reach of the countries of origin of the contributing authors. Then from the mapping of keywords, it shows that the focus of Community Based Tourism research is quite varied. The main research results that are widely discussed are about community participation, while the aspects that are less discussed are about income equality. Therefore, further research on Community Based Tourism can focus on the economic aspect.